An extraordinary new species from western Anatolia (Türkiye): Umbilicus choripetalus (Crassulaceae) - Yildirim, Hasan; Özüdoğru, Bariş; Özdöl, Tuğkan; Can, Ilgin Deniz; Pirhan, Ademi Fahri; Balos, Mehmet Maruf; Arasan, Şükrü (Phytotaxa, 2025)
Umbilicus choripetalus is described as a new species from Ödemiş district in the province of İzmir in western Anatolia (Türkiye), based on morphological and molecular evidence. Diagnostic characteristics, a full description, and comprehensive photographs are provided. It is morphologically related to U. tropaeolifolius and U. paniculiformis, but can be distinguished both morphologically and ecologically. The most notable distinguishing feature is the corolla morphology: U. choripetalus has a stellate corolla with deeply divided petals, a unique feature within the genus. Other characteristic features include a linear and obtuse calyx structure and longer pedicels (2–15 mm). This species is distinct in its sparsely branched inflorescence, bearing a significantly reduced number of flowers (three to seventeen) arranged in a raceme or simple panicle. This situation starkly contrasts with profusely flowered and more robust paniculate inflorescences in related taxa. U. choripetalus is ecologically confined to volcanic substrates. Its relatives are restricted to limestone, indicating a significant degree of edaphic specialization . The combination of its morphological and ecological traits unequivocally establishes Umbilicus choripetalus as a distinct and isolated lineage within the genus Umbilicus.